Primordial nucleosynthesis: first instants after big bang - Assunção, Marlete (Cadernos de Astronomia, 2023)
Primordial nucleosynthesis is the central theme of this article that describes the evolution of the universe from its origin to the first 3 minutes after the big bang. The universe is characterized as a cauldron of particles. As the universe expands and temperature decreases, a competition takes place between the creation and annihilation of particles, leading to the formation of the first light nuclei, such as hydrogen, deuterium, tritium, lithium, beryllium and boron. The formation of these nuclei is presented from the point of view of Nuclear Physics.